Comparison of the Nutritional and Taste Characteristics of 5 Edible Fungus Powders Based on the Composition of Hydrolyzed Amino Acids and Free Amino Acids - Jian Li; Junmei Ma; Sufang Fan; Shengquan Mi; Yan Zhang (Journal of Food Quality)
The nutritional characteristics and taste of some edible fungus powders were scientifically evaluated and compared. Five common edible fungus powders were used as test materials (Agrocybe chaxinggu edible fungus powder, Pleurotus citrinopileatus edible fungus powder, Flammulina velutipes edible fungus powder, Lentinus edodes edible fungus powder, and Hericium erinaceus edible fungus powder). The hydrolyzed amino acid and free amino acid content were measured by an automatic amino acid analyzer, and the ratios of hydrolyzed amino acid and free amino acid components and the taste characteristics of these eatables were systematically compared. The results showed that the total amount of hydrolyzed amino acids contained in the 5 edible fungus powders was between 2.583 and 14.656 g/100 g. The total amount of free amino acids contained in the 5 edible fungus powders was between 0.550 and 2.612 g/100 g. Comparative analysis of the mass fractions and composition of amino acids indicated that Pleurotus citrinopileatus edible fungus powder best met the ideal protein standard. The taste characteristics of protein were evaluated by calculating the taste active value (TAV) of taste-producing free amino acids. The most significant TAV values of the 5 edible fungus powders appeared in glutamic acid, and this amino acid is an umami amino acid. Principal component analysis (PCA) suggested that four principal components could reflect all the information on the free amino acids with a total cumulative variance contribution rate of 100%, and three principal components could reflect most of the information on the hydrolyzed amino acids with a total cumulative variance contribution rate of 99.143%, which could represent the main trends of free amino acids and hydrolyzed acids in edible fungus powder. The comprehensive evaluation model was established, and the comprehensive score indicated that Agrocybe chaxinggu edible fungus powder had the best comprehensive amino acid quality.